(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A significant plant with numerous traditional therapeutic properties is kalanchoe pinnata. This literature review’s primary goal was to provide background knowledge for K. pinnata drug discovery research. The pharmacological properties of this plant were discovered to include, neuropharmacological, anticonvulsant, anthelmintic, antimicrobial activity, antioxidant activity,analgesic,antidiabetic,woundhealing,antinociceptive,hepatoprotective and immunosuppressive. Both cutaneous leishmaniasis and cadmium-induced nephrotoxicity were significantly protected from by quercetin’s high oral effectiveness. The antibacterial action of K. pinnata may be attributed to two new novel flavonoids. K. pinnata had the potential to be used as chemotherapy preventatives A key element of the K. pinnata extract that protects against a severe allergic response is the flavonoid quercitrin. The evidence-based information provided in this literature review of the pharmacognostic, phytoconstituent, and pharmacological activity of the plant K. pinnata may be useful to researchers conducting more sophisticated qualitative studies.